The Relationship between Teachers’ Occupational Professionalism and Organizational Alienation - Yilmaz Ilker Yorulmaz; Yahya Altinkurt; Kursad Yilmaz (Educational Process: International Journal)
The purpose of this study is to determine the relationship between occupational professionalism and organizational alienation levels of teachers. The study is designed as a survey model. The sample of the study consists of 303 teachers working in the Mugla province of Turkey. Participants were selected by using the disproportionate cluster sampling technique. Data was collected through the application of the Teachers’ Occupational Professionalism Scale and the Work Alienation Scale. Descriptive statistics, t-test, ANOVA and correlation analyses were used to analyze the data. Based on the findings, the participant teachers’ level of occupational professionalism is high. Among the occupational professionalism dimensions, teachers consider they have professional awareness the most. This is followed by emotional labor, contribution to organization, and personal development. Teachers’ occupational professionalism differ according to gender and school type variables, while it does not differ according to seniority and time in service at the current school. The participant teachers’ organizational alienation is low. Among the alienation dimensions, teachers consider alienating the school the most, even if its level is low. This is followed respectively by powerlessness, isolation and meaninglessness dimensions. Teachers’ organizational alienation differs according to gender, school type, seniority and time in service at the current school variables. There are significant relationships between alienation and occupational professionalism levels of teachers.